Mujica como icono = Mujica as an Icon - Natalia Costa Rugnitz; Ignacio Bárcena Ricci (H-ermes: Journal of Communication, 2015)
Mujica as an Icon. José “Pepe” Mujica established in Uruguay, between 2010 and 2015, a political era of long and complicated maturation, giving this small country of three million inhabitants an unprecedented international projection and, at the same time, becoming himself a symbol. Being a philosophical and a mediatic figure also, this peculiar and extremely paradoxical character has just concluded a government in which he seemed to have fulfilled his own destiny, and at the same time that of the whole Nation. Controversial both in his political measures and in his private way of life, “Pepe”, as his fellows call him, has combined in his unusual person the reality of the countrymen, so typical of our emergent continent, and an exercise of citizenship which we will probably not be able to find again easily. In the following article we intend to offer a critical review of his life and deeds, with the intention of understanding the reasons that turned him into the contemporary icon he has become.